Diseño de prototipo de vivienda rural sostenible aplicando técnicas de autoconstrucción con materiales vernáculos en el Municipio de Curití Santander (2023)
The document refers to the situation of rural housing in the Cuchicute village, La Cantera sector, in the municipality of Curití, Department of Santander, which are in precarious conditions and do not have essential public services, a situation that led to the community to conditions of inequality.